Electronic band-structure and optical constants of Pb2GeS4: Ab initio calculations and X-ray spectroscopy experiments - Vu, Tuan V.; Lavrentyev, A. A.; Gabrelian, B. V.; Ananchenko, L. N.; Parasyuk, Oleh V.; Karaim, Olha; Khyzhun, O. Y. (My University, 2018)
The electronic band-structure of the ternary sulfide Pb2GeS4 was investigated by combining experimental and theoretical methods. Binding energy (BE) values of core electrons of Pb2GeS4 are measured employing X-ray photoelectron spectros copy (XPS) for as-synthesized and treated with Ar+-ions crystal surfaces. The XPS measurements indicate that Ar+-ion treatment does not change the BE values of the core-level electrons of atoms constituting the Pb2GeS4 single crystal as well as peculiarities of the XPS valence band (VB) spectrum. The treatment does not cause changes in the crystal surface stoichiometry. The band-structure calculations based on density functional theory (DFT) reveal total density of states and partial densities of states of Pb2GeS4 within different exchange–correlation approximations. The best fit with the experiment is derived when the DFT calculations of Pb2GeS4 employ modified Becke-Johnson potential with Hubbard-corrected func tional and taking into account spin–orbit (SO) interaction. The calculations indicate that top and upper portion of the VB is composed mainly by S 3p states, its central portion is formed by Ge 4p and S 3p states, while contributions of Pb 6s states dominate at its bottom with slightly smaller contributions of Ge 4s states as well. Contributions of unoccupied Pb 6p states dominate at the conduction band (CB) bottom. Regarding the occupation of the VB by Ge 4p and S 3p states, the theoretical data are confirmed experimentally by matching the XPS VB spectrum on a common energy scale with the X-ray emission spectra representing the valence S p and Ge p states. The present calculations yield that the VB maximum is positioned at the Y point, while the CB minimum at the Г point; this fact indicates that Pb2GeS4 sulfide is an indirect-gap material. The principal optical constants are also elucidated using the ab initio DFT calculations.